Foreign direct investment into transition economies: Are the Balkans different? - Saul Estrin; Milica Uvalic (London School of Economics and Political Science (LSE), European Institute, 2013)
The paper explores the determination of foreign direct investment (FDI) into the Balkan transition economies – Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Macedonia, Montenegro, Romania and Serbia. Detailed FDI inflows to Southeast Europe (SEE) are analysed to determine the main differences in the volume, timing and sectoral structure of FDI within the region and in comparison to the Central East European countries. A gravity model to all transition economies during 1990-2011 is then estimated to assess whether the factors driving FDI to the Western Balkans are different. They are found to be so; even when size of their economy, distance, institutional quality and prospects of EU membership are taken into account, Western Balkans countries receive less FDI. These issues are of high policy relevance for the Balkan economies and ought to contribute to the current debate on the 'new growth model'.
Keywords: P3; O4; F2; 330; foreign direct investment; Balkans; transition